Heart rate variability as a physiological indicator or mental toughness - Papantoniou, Adamos (2016)
Mental toughness is gaining prominence in sport psychology since athletes themselves, coaches, members of the press, sports commentators and sports psychologists have cited mental toughness as one of the most important psychological characteristics in elite sports. Even so, an extensive review of the available literature leads to the conclusion that there is a lack of a precise and widely accepted definition of mental toughness, while its conceptualization remains challenging. Therefore, based on the existing literature concerning physiological toughness (Dienstbier, 1989), this study examines through an innovative psychophysiological perspective how mental toughness operates, and thus contributes to a better understanding of the concept of mental toughness. The purpose of this study was to investigate athletes’ (N = 18) and their respective coach’s perceptions and appraisals of the athletes’ levels of mental toughness (MT) in elite soccer. For this purpose, the Sports Mental Toughness Questionnaire (SMTQ) was used to assess perceptions and appraisals of MT. In addition, the levels of the athletes’ Heart Rate Variability (widely used as an indicator of Autonomous Nervous System and therefore physiological marker of stressors; see Task Force, 1996) were measured, before and during the pre-season preparation period. Existing literature suggests that, the mental and physical demands of the preseason preparation period are relatively too high compared with the rest of the competitive season and this can explain the increased numbers of injuries occurring during that period (Woods, 2002). Overall, results revealed significant associations between athletes’ Heart Rate Variability and the three components of mental toughness (Control, Confidence and Constancy). Specifically, as appear from the Quick Recovery Tests, the Nocturnal Measurements and coach’s subjective opinion on athletes’ levels of mental toughness, coaches tend to perceive as more mentally tough the athletes who usually have a “suitable, positive stress” which keeps them “alert”, in a “constant readiness” and “always ready for fight”. From an applied perspective, this study suggests that sport psychologists and practitioners may identify a need to enrich an athlete’s stress-coping techniques, just by observing heart rate variability patterns and the modulation of autonomous nervous system.